Is time ripe for a currency union in emerging East Asia? The role of monetary stabilisation - Marcelo Sánchez (European Central Bank (ECB), 2005)
This paper assesses the prospects for monetary integration between Emerging East Asian (EEA) economies. Our empirical analysis is based on a simple analytical framework for currency unions of small open economies, with a focus on the conduct of monetary policy in the presence of different types of shocks. Our empirical analysis looks at a number of supply-side characteristics of EEA countries, distinguishing between aggregate and tradable sector structural features. Moreover, we discuss the evidence on the cross-country variation of disturbances hitting the region. Our study indicates that, at present, EEA economies exhibit a high degree of cross-country supply diversity, while there is no compelling evidence that shocks are highly correlated across the region.
Keywords: E52; E58; F33; F40; 330; Currency union; East Asia; emerging economies; stabilisation; Währungsunion; Geldpolitik; Schock; Schwellenländer; Ostasien